“Evaluación de la resistencia natural de maderas de cinco especies forestales al ataque de termites en Tarapoto – San Martín” - Chávez Panduro,Juan Pablo (1997)
Blocks of five tree species were studied in terms of its resistance to the attack of Crxptotermes brevis Walker, and Nasutitermes corniger Motchulski, forced feeding and food selectivity tests, and tasted the repellency of damp sawdust of these named wood to the second of the termites. Those records averages of losses of weight in the samples of wood were analyzed by the test of Duncan, applied to a level of significance of 5%. The values expressed in percentages of survival of Cryptotermes brevis Walker, in the test of power •forzada and Nasutitermes corniger Motchulski in wet sawdust repellency test were analyzed in the form similaF. In order to correct errors caused by the leaching of extractives in the damp substrate, in the evidence of selectivity and force-feeding of e';:; you last made a visual assessment of data on the wooden blocks used the results...